Diagnostic value of glucose transporter 1 and 3 (GLUT1 and GLUT3) mRNA level in postmenopausal women with urinary bladder cancer - Krześlak, Anna; Jóźwiak, Paweł; Forma, Ewa; Bryś, Magdalena; Woźniak, Paweł; Wikosz, Jacek; Lipiński, Marek; Różański, Waldemar (Menopause Review/Przegląd Menopauzalny, 2012)
Purpose : The aim of the study was to evaluate the usefulness of glucose transporters (GLUT1 and GLUT3) mRNA level for bladder cancer diagnosis in postmenopausal women. Material and methods : Glucose transporters expression was measured by a real-time polymerase chain reaction (real-time PCR) assay in urine obtained from 46 postmenopausal women with bladder cancer and 37 healthy women. Results : GLUT1 expression was found in urine of both healthy women (74%) and bladder cancer patients (82%). GLUT3 expression was not detected in urine of healthy persons but it was found in 62% of bladder cancer samples. A positive expression of poorly differentiated bladder cancers (G2, G3) showed a significantly higher GLUT1 expression than G1 tumors. Similarly, GLUT 3 transcript level was significantly higher in G2 and G3 in comparison to G1 bladder cancers. Analogous results were obtained for both genes in relation to the clinical stage (ta-T1 vs. T2-T4). There was no relationship between the expression of studied genes and recurrence. Conclusions : Analysis of the glucose transporters expression in the urine of postmenopausal women with bladder cancer appears to be a useful diagnostic indicator of the disease.